Plastics flammability handbook principles, regulations, testing, and approval - Troitzsch, Jürgen (Hanser ; Hanser Gardener, 2004)
The completely revised and updated third edition of this handbook covers all aspects of plastics flammability from fundamentals to the detailed description of national and international regulations, standards, test methods, and the approval procedures for plastics and plastic components in various fields of application. This unique and comprehensive handbook is an essential reference for everyone concerned with plastics flammability. This book is particularly welcome in simplifying the difficult and often confusing area of national regulations and fire test procedures. Plastics and Rubber International "Troitzsch's work will continue to be a reference book which fire testers, as well as plastics technologists and regulators, should have within arm's reach." Polymer International
Rev. ed. of: International plastics flammability handbook / Jürgen Troitzsch. c1990.
Keywords: Plastics -- Flammability -- Handbooks, manuals, etc.; elektronické knihy; electronic books